2007
DOI: 10.1192/bjp.bp.106.025353
|View full text |Cite
|
Sign up to set email alerts
|

Burden on caregivers of people with schizophrenia: Comparison between Germany and Britain

Abstract: National differences in family burden may be related to different healthcare systems in Germany and Britain. Support for patients with schizophrenia may be shifted from the professional to the informal healthcare sector more in Britain than in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
80
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 28 publications
16
80
0
12
Order By: Relevance
“…Previous studies generally agree that a severe level of symptoms affects the caregiver burden (2,8,9). In contrast, one recent study from Turkey reported no correlation between symptom severity and caregiver burden (4).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies generally agree that a severe level of symptoms affects the caregiver burden (2,8,9). In contrast, one recent study from Turkey reported no correlation between symptom severity and caregiver burden (4).…”
Section: Introductionmentioning
confidence: 96%
“…We used the European Schizophrenia Cohort (EuroSC) – a naturalistic 2-year follow-up of a cohort of 1,208 European schizophrenia patients [14]. Indeed, the EuroSC cohort has been extensively used in past research, which focused on investigating treatment efficacy [15], patients’ quality of life [1618], employment [19], social contact [20,21] and subjective feelings of security and safety [22], as well as assessing caregiver burden [23] and quantifying direct health care costs associated with managing the disease [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…(10) The level of QOL in caregivers of the mentally ills has been found to be associated with various factors including illness factors in patients and psychosocial background of the caregivers. Severity of symptoms, illness duration, level of disabilities, perceived stigma (11)(12)(13)(14)(15)(16)(17)(18), being female caregivers with nuclear family (19), being older with lower socioeconomic status (12) and recent life crisis (20) were found to be associated with lower QOL.…”
Section: Introductionmentioning
confidence: 99%